Thermophysical Properties of Cryoprotectants. II. Dynamic Viscosity of Some Cryoprotectants, Their Solutions and Mixtures - Todrin, A. F.; Popivnenko, L. I.; Kovalenko, S. Ye. (Problems of Cryobiology and Cryomedicine, 2010)
The article represent summarized literature data and derivation of polynomial equations to calculate the dynamics viscosity of water, 21 pure cryoprotective agents and aqueous solutions of three cryoprotective agents in different concentrations depending on temperature. Empirical equations for various concentration and temperatures were obtained to calculate dynamic viscosity of aqueous solutions of NaCl and KCl, aqueous solutions of 38 cryoprotective agents and 18 mixtures of some cryoprotectants.